2018
DOI: 10.1109/jstqe.2018.2814786
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Yb:KGW Laser, CW or Q-Switched, Enabled by Dual-Axis Tilt of an MOEMS Mirror

Abstract: The experimental proof-of-concept demonstration of an end-pumped Yb:KGW laser with tunable spectral and temporal output characteristics is reported. For the first time, tuning of both of these characteristics in a solid-state laser is achieved simultaneously using a single electrothermally actuated micro-opto-electromechanical systems (MOEMS) micromirror with controllable tilt angle in two dimensions. In a continuous-wave mode, a wavelength tuning range of 22 nm with <0.3 nm linewidth was achieved by using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Paterson A. [29] experimentally demonstrated wavelength tunable end-pumped Yb: KGW laser with simultaneous Q-switching using a single MOEMS mirror. He found that continuous tuning range of 22 nm and 15.3 nm was achieved under continuous-wave (CW) and Q-switched operation respectively for an end-pumped Yb: KGW laser.…”
Section: Micro Switchesmentioning
confidence: 99%
“…Paterson A. [29] experimentally demonstrated wavelength tunable end-pumped Yb: KGW laser with simultaneous Q-switching using a single MOEMS mirror. He found that continuous tuning range of 22 nm and 15.3 nm was achieved under continuous-wave (CW) and Q-switched operation respectively for an end-pumped Yb: KGW laser.…”
Section: Micro Switchesmentioning
confidence: 99%
“…In this paper, we report a frequency output MEMS based gas flow sensor that uses a combination of piezoelectric actuation and electrothermal heating to operate in a heated resonating configuration. The sensor design employs a triple-beam cantilever, which is adapted from an electrothermal actuator design used as a component in optical MEMS devices that have been employed for imaging [17] and laser control purposes [18]. The sensor uses thermally-induced changes of the resonance frequency of the silicon triple-beam cantilever structure to measure gas flow.…”
Section: Introductionmentioning
confidence: 99%
“…Scanners with high angular range and improved resonance frequency have been demonstrated [3,4]. These have been integrated in applications ranging from laser engineering to biomedical imaging [5,6]. While thermal actuation has an inherently slower response than other techniques due to thermal time constants, the advantage of easy static tilt angle addressing and 2D operation makes them an interesting prospect for full random access imaging.…”
Section: Introductionmentioning
confidence: 99%